Estimasi Parameter Model Nonlinear Menggunakan Analisis Sensitivitas dan Pengoptimalan Berbasis Turunan - Tua A. Tamba (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2018)
Model estimation based on the observation data of a system’s states is an important subject in the study of dynamical systems. Maximum likelihood (ML) estimation is a stochastic estimation method which can be used to obtain an optimal set of parameter based on noisy measurements. This paper describes the method and implementation of the ML estimator to identify an optimal parameter set in a discrete-time nonlinear state space model. In particular, the optimal parameter set is defined as the value that minimizes the error between the actual and estimated model outputs of the system. This paper discusses a gradient-based optimization that is equipped with sensitivity analysis method for searching such a parameter set. Simulation results which describe an implementation of the proposed estimation method in a nonlinear system model are also discussed.